2014
DOI: 10.1371/journal.pone.0106072
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Essential Medicines for Diabetes in Low and Middle Income Countries: A Survey of 32 National Essential Medicines Lists

Abstract: AimDiabetes is a growing burden especially in low and middle income countries (LMICs). Inadequate access to diabetes care is of particular concern and selection of appropriate diabetes medicines on national essential medicines lists (NEMLs) is a first step in achieving adequate access. This selection was studied among LMICs and influences of various factors associated with selection decisions were assessed.MethodsCountries were studied if they employed NEMLs for reimbursement or procurement purposes. Presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 27 publications
3
28
1
1
Order By: Relevance
“…Other factors include insufficient or inadequate use of insulin, which is often not available , too expensive, or difficult to use because of patients unwillingness or inability to do self‐monitoring of blood glucose . Even metformin and sulphonylurea derivates, widely used and cheap diabetes drugs, are often not available or prohibitively expensive .…”
Section: Discussionmentioning
confidence: 99%
“…Other factors include insufficient or inadequate use of insulin, which is often not available , too expensive, or difficult to use because of patients unwillingness or inability to do self‐monitoring of blood glucose . Even metformin and sulphonylurea derivates, widely used and cheap diabetes drugs, are often not available or prohibitively expensive .…”
Section: Discussionmentioning
confidence: 99%
“…The WHO publishes a Model List of Essential Medicines that provides a framework from which other countries can develop their National Essential Medicines List (NEML). NEMLs are important in ensuring countries appropriately prioritize their expenditure on evidence-based, cost-effective medicines 74. However, only 38% of 15 sub-Saharan countries had updated their NEML in the past 5 years 64.…”
Section: Medication Availabilitymentioning
confidence: 99%
“…Studies in developed countries have shown that diabetic patients who were older, had high co-morbidity burdens, were from an indigenous group, and had relatively low incomes, were less able to access medications and care (68). In LMICs, barriers to diabetes medication include the affordability and availability of essential diabetes medications comprising insulin, glibenclamide, and metformin (9, 10). …”
Section: Introductionmentioning
confidence: 99%